Comparison of different tissue clearing methods and 3D imaging techniques for visualization of GFP-expressing mouse embryos and embryonic hearts - Kolesová, Hana; Čapek, Martin; Radochová, Barbora; Janáček, Jiří; Sedmera, David (Histochemistry and cell biology, 2016)
Our goal was to find an optimal tissue clearing protocol for whole-mount imaging of embryonic and adult hearts and whole embryos of transgenic mice that would preserve green fluorescent protein GFP fluorescence and permit comparison of different currently available 3D imaging modalities. We tested various published organic solvent- or water-based clearing protocols intended to preserve GFP fluorescence in central nervous system: tetrahydrofuran dehydration and dibenzylether protocol (DBE), SCALE, CLARITY, and CUBIC and evaluated their ability to render hearts and whole embryos transparent. DBE clearing protocol did not preserve GFP fluorescence; in addition, DBE caused considerable tissue-shrinking artifacts compared to the gold standard BABB protocol. The CLARITY method considerably improved tissue transparency at later stages, but also decreased GFP fluorescence intensity. The SCALE clearing resulted in sufficient tissue transparency up to ED12.5; at later stages the useful depth of imaging was limited by tissue light scattering. The best method for the cardiac specimens proved to be the CUBIC protocol, which preserved GFP fluorescence well, and cleared the specimens sufficiently even at the adult stages. In addition, CUBIC decolorized the blood and myocardium by removing tissue iron. Good 3D renderings of whole fetal hearts and embryos were obtained with optical projection tomography and selective plane illumination microscopy, although at resolutions lower than with a confocal microscope. Comparison of five tissue clearing protocols and three imaging methods for study of GFP mouse embryos and hearts shows that the optimal method depends on stage and level of detail required.
Keywords: Heart; myši; Imaging, Three-Dimensional; Mice, Transgenic; Green fluorescent protein (GFP); Embryo; Confocal microscopy; myši transgenní; zvířata; Mice; Optical projection tomography; Tissue transparency; zobrazování trojrozměrné; srdce; Green Fluorescent Proteins; zelené fluorescenční proteiny; Animals